Micro and Small Enterprise Development: Modeling the Triangle of Business Consulting, Knowledge Absorption Capacity, and Innovation in Indonesia - Saepudin, Didin; Agusiady, Ricky; Aripin, Zaenal (PT. Kreatif Indonesia Satu, 2024)
Micro and Small Enterprise (MSE) development has an undeniable role in Indonesia's economic dynamics. The success of MSEs in facing challenges and achieving sustainable growth is key to the country's economic progress. This study aims to detail and understand the impact of the business consulting triangle, knowledge absorption capacity, and innovation on the development of MSEs in Indonesia. The research method used involved an in-depth literature review and a qualitative approach. The literature review opened up horizons of understanding on key concepts related to MSEs, while the qualitative approach provided the ability to explore and understand the broader context and dynamics affecting MSEs. The results of this study reveal that the triangle of business consulting, knowledge absorption capacity and innovation plays an important role in forming the foundation of MSE growth. Successful implementation of this model can help MSEs optimize their potential, improve competitiveness and contribute to national economic development. This research provides in-depth insights for stakeholders, government and businesses related to MSEs in Indonesia. The implications of these findings can be used as a basis for designing more effective policies, strateg